Meroterpenoids produced by Pseudocosmospora sp. Bm-1-1 isolated from Acanthus ebracteatus Vahl. (June 2019) - Nakamura, Tomoki; Suzuki, Takuma; Rudianto Ariefta, Nanang; Koseki, Takuya; Aboshi, Takako; Murayama, Tetsuya; Widiyantoro, Ari; Kurniatuhadi, Rikhsan; Malik, Abdul; Annas, Suwardi; Harneti, Desi; Maharani, Rani; et al.
Graphical abstract: Highlights: Meroterpenoids were isolated from endophytic fungus Pseudocosmospora sp. Bm-1-1. The structures of diterpenes were determined by NMR and MS studies. Compounds5, 6 and8 restored growth of a Saccharomyces cerevisiae mutant strain. Compounds3 and8 had cytotoxic activity against HL60 cells (3 : IC50 = 24.1 μM and8 : IC50 1.6 μM). Abstract: Fractionation of ethyl acetate extract obtained by culturing the endophytic fungus Pseudocosmospora sp. Bm-1-1 resulted in the isolation of four new meroterpenoids, cosmosporin A (1 ), 6-carboxy-cosmosporin A (2 ), rel -(6a S, 10a R )-Δ 9 -tetrahydrocannabiorcolic acid B (3 ) and 8′-hydroxy-cannabiorcichromenic acid (4 ), in addition to four known compounds5 –8 . Structures were elucidated by spectral analysis, as well as by directly comparing the spectral data of new compounds with those of known compounds. Cannabiorcichromenic acid (5 ), decarboxy-cannabiorcichromenic acid (6), and rel -(6a S, 10a R )-decarboxy-Δ 9 -tetrahydrocannabiorcolic acid B (8 ) restored growth of a Saccharomyces cerevisiae mutant strain involving Ca 2+ signal transduction. Furthermore, compounds3 and8 had cytotoxic activity against HL60 cells (3 : IC50 = 24.1 μM and8 : IC50 1.6 μM).